'Aamir's just a dork': Ms. Marvel's re-vision of Islam in America. Issue 2 (4th March 2022) - Modarres, Andrea
ABSTRACT: Much of the scholarship to date on the phenomenally popular Kamala Khan focuses on ways this titular character of the Ms. Marvel comic series complicates constructions of gender, religion, and immigration. This article endorses such claims, but instead highlights Kamala's older brother, Aamir, arguing that his character constitutes a powerful counter narrative that refutes pervasive negative stereotypes about American Muslim men in both public and private realms. Over the first few years of the series, Aamir's character evolves from unworldly and typically irritating older brother to loving husband and father, in the process complicating one-dimensional negative stereotypes of Muslim men in the domestic arena. When he is targeted by supervillains in an attempt to radicalise him into terrorism, Aamir's refusal to accept a warped version of Islam not only reinforces the complexities of Muslim beliefs and practices but also challenges readers to acknowledge their own potential roles in accepting and perpetuating harmful misrepresentations. In the process, the comic's illustration of the political and social marginalisation and oppression experienced by Muslims in our theoretically pluralistic society implicitly positions Aamir, as well as Kamala, as an argument for equity and justice.